A review of climate change impacts on urban soil functions with examples and policy insights from England, UK. (3rd September 2013) - Rawlins, B. G.; Harris, J.; Price, S.; Bartlett, M.
Abstract: As of 2010, more than half of the global population resides in urban areas and relies to some extent on the functions, services and natural capital provided by urban soils. Greater extremes in climate predicted for the coming decades will impact on these urban soil functions to varying degrees. We provide an inventory of urban soil functions based on an extension to the typology of the Millennium Ecosystem Assessment (i.e. we added a 'carrying function' to those of supporting, regulating, provisioning and cultural functions) and review the climate drivers that are likely to have the most significant impacts upon them, using urban soils of England as an exemplar. We identify knowledge gaps, as in areas such as carbon cycling and storage, disease regulation and cultural services. We assess adaptation measures, which may ameliorate these potential, climate‐change‐related impacts including changes in construction practices, developments in green architecture and development proposals under the planning regime. We discuss the lack of policies relating to urban soils and the problem associated with monitoring their functions, as is often the case, when large quantities of soil are removed and replaced, leading to major transformation of soil properties, which may be unrelated to pedogenic processes.